A fluorescent aptasensor for ATP based on functional DNAzyme/walker and terminal deoxynucleotidyl transferase-assisted formation of DNA-AgNCs. Issue 4 (24th January 2023) - Cai, Shixin; Chen, Xin; Chen, Haohan; Zhang, Yuting; Wang, Xiaoli; Zhou, Nandi
Abstract : Combination of split aptamer and DNAzyme/walker with terminal deoxynucleotidyl transferase-assisted formation of DNA-AgNCs to construct a fluorescence biosensor for ATP. Abstract : The development of sensitive adenosine triphosphate (ATP) sensors is imperative due to the tight relationship between the physiological conditions and ATP levels in vivo . Herein, a fluorescent aptasensor for ATP is presented, which adopts a strategy that combines a split aptamer and a DNAzyme/walker with terminal deoxynucleotidyl transferase (TDT)-assisted formation of DNA-AgNCs to realize fluorescence detection of ATP. A multifunctional oligonucleotide sequence is rationally designed, which integrates a split aptamer, a DNAzyme and a DNA walker. Both multifunctional oligonucleotide and its substrate strand are connected to the surface of Fe3 O4 @Au nanoparticles via Au–S bonds. The existence of ATP can induce the formation of the complete aptamer, and then activate the DNAzyme to circularly cleave the substrate strand, leaving 2′, 3′-cyclophosphate at the 3′end of the strand. This blocks the polymerization of dCTP to form poly(C) even in the presence of TDT and dCTP, due to the lack of free 3′-OH. In contrast, when ATP is absent, the DNAzyme/walker cannot work and then TDT catalyzes the formation of poly(C) at the free 3′-OH of the substrate strand, which is subsequently utilized as the template to prepare DNA-AgNCs. The fluorescence response derived from AgNCs thus reflects the ATP concentration. Under the optimum conditions, the aptasensor shows a linear response range from 5 nM to 10 000 nM, with a detection limit of 0.27 nM. The level of ATP in human serum can be effectively measured by the aptasensor with good recovery, indicating its application potential in medical samples.